How does land management contribute to the resilience of Mediterranean forests and rangelands? A participatory assessment. (15th August 2018) - Jucker Riva, Matteo; Baeza, Jaime; Bautista, Susana; Christoforou, Michalakis; Daliakopoulos, Ioannis N.; Hadjimitsis, Diofantos; Keizer, Jan Jacob; Liniger, Hanspeter; Quaranta, Giovanni; Ribeiro, Cristina; Salvia, Rosanna; Tsanis, Ioannis K.; et al.
Abstract: In Mediterranean forests and rangelands, the supply of important ecosystem services can decrease or cease as a consequence of disturbances and climatic oscillations. Land managers can sometimes prevent or mitigate the negative effects of disturbances through appropriate land management choices. In this study, we assess the contribution of land management practices (LMPs) to the resilience of eight Mediterranean forests and rangelands to multiple disturbances. The study uses a transdisciplinary approach, involving scientists, land managers, and local administrators. Data about disturbances, ecosystem services, the role of LMPs, and the resistance of LMPs to disturbances are combined using a semiquantitative index and analysed to evaluate how the LMPs implemented are suited to the disturbances affecting each study site. Our results indicate that the practices analysed are particularly effective in improving resilience of ecosystems against wildfires and torrential rainfalls. However, droughts are more difficult to address, and the examined practices were heavily affected by their occurrence. Tree planting appears to be highly affected by disturbances. Practices that selectively reduce the amount of vegetation appear to be beneficial in fostering recovery of ecosystems. Our assessment also suggests that it is particularly difficult to increase resilience to droughts and fires simultaneously. Practices that aimed to mitigate the impact of land use did not always prove valuable in terms of resilience. Finally, study sites that included efforts to address disturbances in their management objectives also displayed practices making the biggest contribution to resilience.